Projected Atlantic overturning slow-down is to be compensated by a strengthened South Atlantic subtropical gyre - Fernanda Marcello; Marcos Tonelli; Bruno Ferrero; Ilana Wainer (Communications Earth & Environment, 2023)
Large ensemble simulations project an intensification of the South Atlantic subtropical gyre with reduced water supply to the North Atlantic due to a weakening of the Atlantic meridional overturning circulation and changes in atmospheric forcing.